Long-Term Risk of Progression to Sustained Hypertension in White-Coat Hypertension with Normal Night-Time Blood Pressure Values - João Faria; José Mesquita Bastos; Susana Bertoquini; José Silva; Jorge Polónia (International Journal of Hypertension)
Background. The long-term prognosis and transition towards sustained ambulatory hypertension (SHT) of white-coat hypertension (WCHT) remain uncertain particularly in those with both normal nighttime and daytime blood pressure (BP) values. Different classification criteria and the use of antihypertensive drugs may contribute to conflicting results. Patients and Methods. We prospectively evaluated for a 7.1 year transition to SHT in 899 nondiabetic subjects free from cardiovascular (CV) events: normotensive (NT) (n = 344; 52, 9% female; ageing 48 ± 14 years); untreated WCHT (UnWCHT n = 399; 50, 1% female; ageing 51 ± 14 years); and treated WCHT with antihypertensive drugs after baseline (TxWCHT n = 156; 54, 4% female; ageing 51 ± 15 years). All underwent 24 h ambulatory BP monitoring (24 h-ABPM) at baseline, at 30 to 60 months, and at 70 to 120 months thereafter. WCHT was at baseline (with no treatment) as office BP ≥ 140/or 90 mm·Hg, daytime BP < 135/85 mm·Hg, and nighttime BP < 120/70 mm·Hg. Development of SHT was considered if daytime BP ≥ 135/or 85 mm Hg and/or nighttime BP ≥ 120/or 70 mm·Hg. Results. Baseline metabolic parameters did not differ among groups. At 30–60 months and at the end of follow-up, development of SHT occurred, respectively, in NT (3.8% (n = 13) and 9.6% (n = 33)) and in UnWCHT (10.1% (n = 40) and 16.5% (n = 66)) (p<0.009). The mean annual increase of average 24 h-systolic BP was 0.48 + 0.93 in NT and 0.73 + 1.06 in UnWCHT, whereas annual SBP in office increased in NT by 1.2 + 0.95 but decreased in UnWCHT by 1.36 + 1.35 mm Hg (p<0.01). Conclusion. Untreated WCHT patients exhibit a faster and a higher risk of developing SHT compared to NT with TxWCHT assuming an intermediate position between them.